2008
DOI: 10.2340/16501977-0259
|View full text |Cite
|
Sign up to set email alerts
|

Positive experiences of encounters with healthcare and social insurance professionals among people on long-term sick leave

Abstract: The majority of the respondents on long-term sickness absence have had positive interactions with healthcare and social insurance. More research is required to determine the impact that such experiences might have on return to work, and how such interactions might be promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 13 publications
4
51
1
Order By: Relevance
“…[4, 13] Consistent with our findings, research in Sweden found that 73% of long-term sick leave survey respondents reported positive interactions with social insurance representatives. [13] Our findings also suggest that patients require knowledge and skills to effectively navigate the health insurance system to obtain information, respond to claims, or correct claims on a timely basis. [19]…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[4, 13] Consistent with our findings, research in Sweden found that 73% of long-term sick leave survey respondents reported positive interactions with social insurance representatives. [13] Our findings also suggest that patients require knowledge and skills to effectively navigate the health insurance system to obtain information, respond to claims, or correct claims on a timely basis. [19]…”
Section: Discussionsupporting
confidence: 89%
“…[8–9] For example, administrative delays in insurance coverage were associated with increased odds of developing chronic disability in a sample of employees with back injuries (n=35,304). [10] Although anecdotal reports abound,[11] there has been little systematic examination of beneficiaries’ reported interactions with insurers in the US[12–13] or of unique issues raised by kidney transplant recipients. A survey of Medicare beneficiaries (n=2,997) found that poorer familiarity with the Medicare program is associated with delayed care, lack of prescription medication use, and poorer overall health.…”
mentioning
confidence: 99%
“…In addition, 'Received useful information', 'Received useful advice and support about paid work' and (17) 97 (17) 13 (17) 'Received encouragement about paid work' significantly correlated with the impact of positive encounters on selfestimated ability to return to work. Descriptive statistics are presented in table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Such factors include how healthcare professionals encounter the sick-listed person. [16][17][18][19] Also emotional responses can affect the ability to return to work. 20 Emotions are evoked and experienced when encountered by other people, especially when encountered by people who are perceived as particularly significant.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have pointed to socio-economic, ethnic or gender differences in how individuals are treated in insurance systems (Lippel 2003;Gravel et al 2010;Leinonen et al 2011), as well as claimants' perceptions of diminished social justice in their interactions with compensation systems (RobertsYates 2003;Strunin and Boden 2004;MacEachen et al 2007;Franche et al 2009). It has been 5 proposed that sick-listed individuals' perceptions of encounters with professionals determine whether the rehabilitation process will be experienced as empowering or disempowering (Müssener et al 2008), and that professionals should focus on health, motivation and pride in their interactions with sick-listed individuals (Svensson and Björklund 2010). Other studies have pointed out how social insurance officials experience ethical dilemmas when balancing insurance regulations and claimants' needs (Stensöta 2010;Ståhl et al 2012).…”
Section: Why An Ethics Approach?mentioning
confidence: 99%